2013
DOI: 10.1111/hepr.12172
|View full text |Cite
|
Sign up to set email alerts
|

Significance of viral status on recurrence of hepatitis B‐related hepatocellular carcinoma after curative therapy: A meta‐analysis

Abstract: The present study suggested that HCC patients with high viral load, genotype C and BCP mutation had a significantly higher risk of recurrence. Antiviral therapy has potential beneficial effects after the curative treatment of HCC in terms of tumor recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…Compared with those with instantaneous high HBV DNA level, patients with persistent high HBV DNA level at resection and follow up had the highest recurrence risk . Meanwhile, in a previous meta‐analysis, our data also proved that high viral load was associated with a significantly higher risk of recurrence after curative therapy of HCC . Theoretically, it is likely that these subjects who have ongoing active HBV replication are more prone to HCC development in remaining liver tissue.…”
Section: Hbv Dnasupporting
confidence: 67%
See 1 more Smart Citation
“…Compared with those with instantaneous high HBV DNA level, patients with persistent high HBV DNA level at resection and follow up had the highest recurrence risk . Meanwhile, in a previous meta‐analysis, our data also proved that high viral load was associated with a significantly higher risk of recurrence after curative therapy of HCC . Theoretically, it is likely that these subjects who have ongoing active HBV replication are more prone to HCC development in remaining liver tissue.…”
Section: Hbv Dnasupporting
confidence: 67%
“…However, in Wu et al .’s study, the significant relationship between precore mutation, V1753, BCP double mutations and the HCC recurrence was not proved . In our previous meta‐analysis, the results also showed that the presence of 1762T/1764A double mutations was significantly associated with HCC recurrence after curative therapy . Additionally, pre‐S deletion was another hot spot mutation which had been extensively investigated.…”
Section: Hbv‐specific Mutationsmentioning
confidence: 89%
“…As the viral load decreases, the genetic stability in hepatocytes is improved that helps further regeneration. In a metaanalysis, the authors reported the decrease in HCC recurrence with decreasing viral load [20]. In the current study, HBV reactivation was seen in 42 (11.7 %) patients after 6 months of initial TACE.…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, the meta-analyses of well-designed non-RCTs have been demonstrated as accurate as RCTs [36]. To the best of our knowledge, two previous meta-analyses were conducted to examine the effect of antiviral therapy with NA on patients with HBV-related HCC after curative treatment [37,38]. The current study was performed on the basis of updated data from recent reports focusing on HBV-related HCC after curative treatment [12,27,32,34].…”
Section: Discussionmentioning
confidence: 99%